Utilization of Intravascular Ultrasound during Carotid Artery Stenting - Hitchner, Elizabeth; Zhou, Wei (International Journal of Angiology, 2015)
For patients at high risk for surgery, carotid artery stenting (CAS) is a viable alternative to help reduce risk of stroke for patients with high-grade carotid artery stenosis; however, a higher incidence of perioperative stroke has been observed in patients undergoing stenting compared to those undergoing open surgery. Intravascular ultrasound (IVUS) is commonly used during coronary artery procedures to help evaluate lesions and to guide stent placement. Multiple groups have sought to determine whether IVUS could also be used during CAS. While IVUS has been shown to be both feasible and safe during CAS, there is limited evidence that demonstrates direct improvement in procedural outcomes. Further studies focusing on clinical outcomes should be conducted in order to justify routine use of this technology during CAS.
Keywords: stroke; carotid stenosis; carotid stent; internal carotid artery; intravascular ultrasound; microemboli; ultrasound